Electrolyte, preparation method thereof and battery
Patent Information
- Application Number
- CN202411219177.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-10
AI Technical Summary
The various lithium sulfide conversion processes generated by lithium sulfur batteries during charging and discharging affect the performance and cycle stability of the battery. Although high donor number solvents can promote reactions, they may lead to unstable electrolyte interfaces and uneven deposition of lithium ions. Increase safety hazards and hinder battery performance.
Asymmetric quaternary ammonium salt methyl trin-butyl ammonium bromide (C13H30NBr) is used as an additive to promote the conversion of polysulfide intermediates through high donor number bromine anions, and combine high-stability ammonium salt large cations to reduce The reactivity of the lithium negative electrode forms a three-dimensional Li2S nucleation growth and solid electrolyte interface to improve battery performance.
It improves the cycle stability and safety of lithium-sulfur batteries, enhances Li+ transmission efficiency, extends the cycle life of the battery and increases the energy density.
Smart Images

Figure CN119297397A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and relates to an electrolyte, a preparation method thereof, and a battery. 13 H 30 A lithium-sulfur battery electrolyte using NBr as an additive, a preparation method thereof, and a lithium-sulfur battery. Background Art
[0002] Lithium-sulfur batteries have a theoretical energy density of up to 2600Wh / kg, which is more than six times the energy density of current commercial lithium batteries. In addition, sulfur is abundant in nature, inexpensive, and environmentally friendly, and is considered a powerful alternative to lithium-ion batteries. However, the practical application of lithium-sulfur batteries is limited by several technical challenges, especially the fact that the sulfur cathode generates a variety of lithium sulfides (LiS) during the charge and discharge process. 2 S x ), the conversion process between different polysulfides will directly affect the battery's charge and discharge performance, cycle stability, etc.
[0003] In the current research context, the composition of the electrolyte is adjusted to achieve efficient conversion of lithium polysulfide and lithium sulfide (Li 2 The regulation of nucleation and growth of S) is a key research direction in lithium-sulfur battery research. Among them, the use of high donor number solvents can promote the transformation of reaction intermediates and the kinetic process of dissolution of long-chain polysulfides, and realize Li 2 S three-dimensional (3D) nucleation can also increase the efficiency of electron transfer, thereby improving the charge and discharge performance and cycle stability of lithium-sulfur batteries. Therefore, in recent years, researchers have begun to focus on the study of high donor number solvents. However, the high reactivity of high donor number solvents with lithium negative electrodes may produce an unstable electrolyte interface layer, which will break during the cycle process, causing accelerated aging of the lithium negative electrode; the uneven deposition of lithium ions will also promote the growth of lithium dendrites, increasing safety hazards; some high donor number solvents also have a high viscosity, which hinders the migration of lithium ions and affects the charge and discharge performance of the battery. In order to reduce the impact of these problems, researchers are exploring the use of less reactive and more stable high donor number solvents or additives to improve the cycle stability and safety of lithium-sulfur batteries. For example, using N-methyl-pyrrolidone (NMP) with a high donor number as an electrolyte additive can establish a unique solvation structure to achieve Li 2 3D nucleation and growth of S. However, such additives often have strong reactivity with lithium anodes, resulting in a significant decrease in capacity after cycling. These studies show that it is necessary to explore advanced electrolyte components that are both compatible with lithium metal anodes and can achieve intermediate conversion pathways. Summary of the invention
[0004] The purpose of the present invention is to provide an electrolyte and a preparation method thereof and a battery. Ammonium salts have great application potential in the field of electrolytes due to their thermal stability, chemical stability, adjustable structure, wide electrochemical stability window and high ionic conductivity. The present invention specifically provides an asymmetric quaternary ammonium salt-methyl tri-n-butyl ammonium bromide (C 13 H 30 NBr) as an additive for a lithium-sulfur battery electrolyte, a preparation method thereof, and a lithium-sulfur battery. The electrolyte can improve the performance of the lithium-sulfur battery and is intended to promote the conversion of polysulfide intermediates through high-donor bromine anions, thereby facilitating the formation of the discharge final product Li 2 The three-dimensional nucleation and growth of S promotes the Li + transport; at the same time, combined with highly stable large cations of ammonium salts, the side reactivity of negative electrode Li is reduced, providing a new way to develop battery technology with higher energy density and longer cycle life.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] The first aspect of the present invention provides an electrolyte, comprising a lithium salt, an ether-based solvent and an additive; the additive is C 13 H 30 NBr, the concentration of the lithium salt is 500-2000 mmol / L, the C 13 H 30 The concentration of NBr is 50-150 mmol / L.
[0007] Use asymmetric quaternary ammonium salt C 13 H 30 NBr as electrolyte additive, C 13 H 30 The long-chain alkyl in NBr can effectively promote the discharge final product Li 2 The 3D nucleation and growth of S promotes the Li + Ion transport promotes sulfur conversion. At the same time, long-chain ammonium cations have low reactivity with lithium negative electrodes, effectively improving the cycle stability of lithium-sulfur batteries.
[0008] Furthermore, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate and lithium bromide.
[0009] Furthermore, the ether-based solvent includes ethylene glycol dimethyl ether and 1,3-dioxolane.
[0010] Furthermore, in the ether-based solvent, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:(1-3).
[0011] A second aspect of the present invention provides a method for preparing an electrolyte, comprising the following steps:
[0012] 1) In a glove box filled with argon, first weigh an appropriate amount of lithium salt according to the desired electrolyte concentration, and add the lithium salt to the pre-mixed ether-based solvent to obtain a basic electrolyte;
[0013] 2) Adding an appropriate amount of additives to the basic electrolyte obtained in step 1) and letting it stand to obtain a uniform and stable electrolyte.
[0014] Furthermore, in step 1), the gas atmosphere is an inert gas, preferably argon; in step 2), during the standing, the standing condition is an argon environment, the standing temperature is room temperature, and the standing time is 12 to 36 hours to ensure that the components in the electrolyte are fully soluble in each other to form a uniform and stable electrolyte with higher conversion efficiency.
[0015] A third aspect of the present invention provides a battery, comprising a positive electrode, a battery separator, a negative electrode and the above-mentioned electrolyte.
[0016] Furthermore, the positive electrode adopts a sulfur-carbon composite material, the battery separator adopts Celgard-2500, Whatman1823-047 or Whatman1825-047, and the negative electrode adopts a metal lithium sheet with a clean surface and no oxidation.
[0017] Furthermore, the sulfur-carbon composite material is elemental sulfur loaded on a carbon material, which is obtained by mixing elemental sulfur and carbon material and then heat treating them, and the loading amount of the elemental sulfur is 1.5-5 mg cm -2 .
[0018] Furthermore, the carbon material is selected from any one of acetylene black, Ketjen Black (KB) or carbon nanotubes.
[0019] Furthermore, the mass ratio of the elemental sulfur and the carbon material is (5-7):(3-5), and in the heat treatment, the heat treatment temperature is 120-200°C, the heat treatment time is 1-24h, and the treatment atmosphere is an inert gas.
[0020] Furthermore, the battery assembly process includes: assembling the positive electrode, battery separator and negative electrode in a glove box filled with argon gas, and injecting the electrolyte into the battery casing to ensure that the electrolyte is in full contact with the positive electrode and the negative electrode.
[0021] Furthermore, the amount of the electrolyte is 20-80 μL / mgS to ensure the electrochemical performance of the battery.
[0022] Compared with the prior art, the present invention has the following characteristics:
[0023] 1) The present invention uses asymmetric quaternary ammonium salt C 13H 30 NBr as an electrolyte additive has obtained a lithium-sulfur battery electrolyte with higher conversion efficiency. It contains bromide anions with a high donor number and combines with highly stable ammonium salts, which can trigger the conversion of polysulfide intermediates, thereby promoting the kinetic process of sulfur during discharge and improving the compatibility with lithium metal anode.
[0024] 2) C of the lithium-sulfur battery electrolyte proposed in the present invention 13 H 30 The long-chain alkyl in NBr additive can effectively promote the discharge end product Li 2 The 3D nucleation and growth of S promotes the Li + Ion transport improves the kinetics of positive electrode oxidation reactions.
[0025] 3) The lithium-sulfur battery electrolyte proposed in the present invention can also change the solvation structure of lithium ions, form a solid electrolyte interface (SEI) on the surface of the lithium negative electrode, effectively inhibit the growth of lithium dendrites, and improve the sulfur utilization rate and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The charge and discharge curves of the button-type lithium-sulfur batteries obtained in Example 5 and Comparative Example 2 in different electrolytes;
[0027] Figure 2 The Li obtained after the charge and discharge test in Example 5 2 SEM images of S deposition;
[0028] Figure 3 The Li obtained after the charge and discharge test in Comparative Example 2 2 SEM images of S deposition;
[0029] Figure 4 is the number of donors for different solvents / anions. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0031] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.
[0032] The sulfur positive electrode adopts a sulfur-carbon composite material, which is obtained by compounding elemental sulfur and Ketjen black. The specific preparation steps include: mixing elemental sulfur and Ketjen black with a mass ratio of (5-7): (3-5) by ball milling, and then heat treating at 120-200°C for 1-24h under inert gas protection to form a sulfur-carbon composite material, wherein the loading amount of elemental sulfur is controlled to be 1.5-5mg cm -2 .
[0033] Examples 1-3 and Comparative Example 1 - Preparation of Electrolyte
[0034] Embodiment 1:
[0035] In an argon-filled glove box, lithium bis(trifluoromethanesulfonyl)imide (LITFSI) was accurately weighed to a final concentration of 1000 mmol / L and dissolved in a pre-mixed ether solvent consisting of ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) (volume ratio of 3:1). According to the experimental design, C 13 H 30 NBr was added to the above solution and completely dissolved under stirring. The solution was allowed to stand for 24 h under argon gas and room temperature to ensure that the components in the electrolyte were fully soluble in each other and to obtain a uniform and stable electrolyte.
[0036] Embodiment 2:
[0037] In a glove box filled with argon, LITFSI and lithium nitrate (LiNO) were accurately weighed to a final concentration of 750 mmol / L. 3 ) and dissolved in a pre-mixed ether solvent consisting of DME and DOL (volume ratio of 2:1). According to the experimental design, C 13 H 30 NBr was added to the above solution and completely dissolved under stirring. The solution was allowed to stand for 24 h under argon gas and room temperature to ensure that the components in the electrolyte were fully soluble in each other and to obtain a uniform and stable electrolyte.
[0038] Embodiment 3:
[0039] In a glove box filled with argon, LITFSI was accurately weighed to a final concentration of 2000 mmol / L and dissolved in a pre-mixed ether solvent consisting of DME and DOL (volume ratio of 1:1). According to the experimental design, C 13 H 30 NBr was added to the above solution and completely dissolved under stirring. The solution was allowed to stand for 12 h at room temperature under argon to ensure that the components in the electrolyte were fully soluble in each other and a uniform and stable electrolyte was obtained.
[0040] Comparative Example 1:
[0041] The difference between this comparative example and Example 1 is that no C 13 H 30 NBr, and the remaining steps are the same as in Example 1.
[0042] Examples 4-5 and Comparative Example 2: Assembly and electrochemical performance testing of button-type lithium-sulfur batteries
[0043] Embodiment 4:
[0044] At room temperature, in an argon-filled glove box, button-type lithium-sulfur batteries were assembled using sulfur cathodes (sulfur and Ketjen black in a ratio of 7:3 treated at 150 °C for 12 h), lithium anodes, and battery separators (Celgard-2500). The sulfur loading in the sulfur cathode was controlled at 2 mg cm -2 , then drop 40μL of the electrolyte obtained in Example 1 onto the positive electrode sheet, cover the diaphragm, drop 40μL of the electrolyte into the center of the diaphragm, and then cover the lithium negative electrode. After the battery is assembled, let it stand at room temperature for at least 12 hours to allow the electrolyte to fully infiltrate the battery components. Subsequently, a constant current charge and discharge test was performed on the battery using a blue electric charge and discharge instrument at a rate of 0.1C within a test voltage range of 1.7V to 2.8V. During the first charge and discharge process, record the open circuit voltage, discharge platform, and charging platform of the battery. After the test, remove the sulfur positive electrode and take a SEM image.
[0045] Embodiment 5:
[0046] At room temperature, in an argon-filled glove box, button-type lithium-sulfur batteries were assembled using sulfur cathodes (sulfur and Ketjen black in a ratio of 7:3 treated at 120 °C for 18 h), lithium anodes, and battery separators (Celgard-2500). The sulfur loading in the sulfur cathode was controlled at 3 mg cm -2 , then drop 40μL of the electrolyte obtained in Example 1 onto the positive electrode sheet, cover the diaphragm, drop 40μL of the electrolyte into the center of the diaphragm, and then cover the lithium negative electrode. After the battery is assembled, let it stand at room temperature for 12 hours to allow the electrolyte to fully infiltrate the battery components. Subsequently, a constant current charge and discharge test was performed on the battery using a blue electric charge and discharge instrument at a rate of 0.1C within a test voltage range of 1.7V to 2.8V. During the first charge and discharge process, the open circuit voltage, discharge platform, and charging platform of the battery were recorded. After the test, the sulfur positive electrode was removed and a SEM image was taken.
[0047] Comparative Example 2:
[0048] At room temperature, in an argon-filled glove box, button-type lithium-sulfur batteries were assembled using sulfur cathodes (sulfur and Ketjen black in a ratio of 7:3 treated at 120 °C for 12 h), lithium anodes, and battery separators (Celgard-2500). The sulfur loading in the sulfur cathode was controlled at 3 mg cm -2 , then add 40μL of the electrolyte obtained in Comparative Example 1 to the positive electrode sheet, cover the diaphragm, add 40μL of electrolyte to the center of the diaphragm, and then cover the lithium negative electrode. After the battery is assembled, let it stand at room temperature for 12 hours to allow the electrolyte to fully infiltrate the battery components. Subsequently, the battery was subjected to a constant current charge and discharge test using a blue electric charge and discharge instrument at a rate of 0.1C within a test voltage range of 1.7V to 2.8V. During the first charge and discharge process, the open circuit voltage, discharge platform, and charging platform of the battery were recorded. After the test, the sulfur positive electrode was removed and a SEM image was taken.
[0049] Figure 1 The charge and discharge curves of the button-type lithium-sulfur batteries obtained in Example 5 and Comparative Example 2 in different electrolytes are shown in FIG. Figure 2 The Li obtained after the charge and discharge test in Example 5 2 SEM images of S deposition, Figure 3 The Li obtained after the charge and discharge test in Comparative Example 2 2 SEM images of S deposition, Figure 4 is the number of donors for different solvents / anions. Figure 1 As can be seen, using the addition of C 13 H 30 The initial capacity of the button-type lithium-sulfur battery assembled with the electrolyte prepared after adding NBr is 1085 mAh / g, which is greater than that of the battery without adding C 13 H 30 The initial capacity of the battery assembled with the electrolyte prepared by NBr (844 mAh / g) is exactly 13 H 30 The addition of NBr improves the initial capacity of the assembled button-type lithium-sulfur battery. Figure 2 and Figure 3 As can be seen, C 13 H 30 The addition of NBr makes the discharge final product Li 2 The deposition morphology of S changes from a passivation film to a 3D particle structure, which promotes the deposition of Li + transport and improve the cathode reaction kinetics.
[0050] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An electrolyte, characterized in that: The invention comprises lithium salt, ether-based solvent and additive; the additive is methyl tri-n-butylammonium bromide, the concentration of the lithium salt is 500-2000 mmol / L, and the concentration of the methyl tri-n-butylammonium bromide is 50-150 mmol / L.
2. The electrolyte according to claim 1, characterized in that The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate and lithium bromide, and the ether-based solvent includes ethylene glycol dimethyl ether and / or 1,3-dioxolane.
3. The electrolyte according to claim 2, characterized in that In the ether-based solvent, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:(1-3).
4. A method for preparing an electrolyte according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: 1) adding a lithium salt to an ether-based solvent to obtain a basic electrolyte; 2) Adding additives to the basic electrolyte obtained in step 1) and allowing the mixture to stand to obtain an electrolyte.
5. The method for preparing an electrolyte according to claim 4, characterized in that: In step 1), the gas atmosphere is an inert gas; in step 2), during the standing, the standing atmosphere is an argon atmosphere, the standing temperature is room temperature, and the standing time is 12 to 36 hours.
6. A battery, characterized in that: The invention comprises a positive electrode, a battery separator, a negative electrode and an electrolyte as claimed in any one of claims 1 to 3.
7. The battery according to claim 6, characterized in that The positive electrode adopts a sulfur-carbon composite material, the battery separator adopts Celgard-2500, Whatman1823-047 or Whatman1825-047, and the negative electrode adopts a metal lithium sheet.
8. The battery according to claim 7, characterized in that The sulfur-carbon composite material is elemental sulfur loaded on a carbon material, and the loading amount of the elemental sulfur is 1.5 to 5 mg cm -2 .
9. The battery according to claim 7, characterized in that The method for preparing the sulfur-carbon composite material comprises: mixing elemental sulfur and carbon material and then heat treating; The mass ratio of the elemental sulfur and the carbon material is (5-7):(3-5). In the heat treatment, the heat treatment temperature is 120-200°C, the heat treatment time is 1-24h, and the treatment atmosphere is an inert gas.
10. The battery according to claim 8, characterized in that The dosage of the electrolyte is 20-80 μL / mg S.